2020
DOI: 10.4102/jtscm.v14i0.475
|View full text |Cite
|
Sign up to set email alerts
|

Physical distribution challenges and adaptations: A qualitative study of South Africa-based organisations operating in emerging African markets

Abstract: This study aims to provide insights into the prevalent physical distribution challenges that organisations face in emerging markets in Africa. Emphasis is placed on the adaptations organisations make to overcome these challenges. The study focused on multinational organisations operating in the fast-moving consumer goods, third-party logistics and retail industry, mostly from the perspective of the South African division. Method:A generic qualitative research design was employed. Twelve semi-structured intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Recognizing the importance of infrastructure investment and maintenance is essential for delivering effective and responsive public services that meet the needs of citizens…" Therefore, role of physical infrastructure and facilities in service delivery is multifaceted and crucial for the effective functioning of inventory management in sector organizations. The study findings concur with those of Kumar, et al (2021) and Mashilo, et al (2020) who found that physical infrastructure, such as warehouses and storage facilities, is essential for inventory management forming indispensable components of inventory management systems in ensuring the application technology adoption regulatory environment, physical infrastructure and facilities in service delivery.…”
Section: Physical Infrastructure and Facilitiessupporting
confidence: 89%
See 1 more Smart Citation
“…Recognizing the importance of infrastructure investment and maintenance is essential for delivering effective and responsive public services that meet the needs of citizens…" Therefore, role of physical infrastructure and facilities in service delivery is multifaceted and crucial for the effective functioning of inventory management in sector organizations. The study findings concur with those of Kumar, et al (2021) and Mashilo, et al (2020) who found that physical infrastructure, such as warehouses and storage facilities, is essential for inventory management forming indispensable components of inventory management systems in ensuring the application technology adoption regulatory environment, physical infrastructure and facilities in service delivery.…”
Section: Physical Infrastructure and Facilitiessupporting
confidence: 89%
“…Physical infrastructure, such as warehouses and storage facilities, is essential for inventory management forming indispensable components of inventory management systems in ensuring the efficiency, organization, and accessibility of inventory (Kumar, et al, 2021;Mashilo, et al, 2020). These spaces provide a secure and organized environment for storing goods, allowing for efficient tracking, easy access, and proper handling.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The higher levels of contamination (p < 0.05) for TBC and CC between the loading and off-loading points in the LTA could be associated with handling during transportation [41], as the trucks that were used to deliver the carcasses were just ordinary vans with no refrigerators. Transportation of products to retail outlets and storage is the most common weak link in the chain [25,42,43].…”
Section: Microbial Counts As Affected By the Abattoir Meat Type And D...mentioning
confidence: 99%